SISTEM INFORMASI GEOGRAFIS POTENSI SUMBER DAYA ALAM DI WILAYAH KABUPATEN BANGGAI KEPULAUAN BERBASIS ANDROID - Utiarahman, Siti Andini; D. Ali, Satriadi (Jurnal Informatika Upgris, 2020)
Geographic Information System (GIS) is an information sistem manages data that has special information that is meant as a computer sistem that has the ability to build, store and manage and display information with geographical significance. As an example is information related to natural resources. Banggai kepulauan is one of the regencies in the province of central Sulawesi and has its capital in salakan. The economy in the regency is proud of the islands related to agricultural activities in accordance with their livelihoods utilizing natural potential. So most of the population is engaged in agriculture, plantations and fisheries. However, because there is no processing industry that is able to absorb natural products, farmer only market these natural products in the form of raw materials. For this reason, the researcher took the initiative to create an android based geographic information sistem so that the large natural potential in the region could be published throughout the Indonesian people. So that through this sistem, anyone who needs information on natural resource potential data of the regency of the archipelago proudly, especially in the agriculture, fisheries and loggin sectors, can easily access it anytime and anywhere through mobile devices in real time.